Theoretical Problems of Legal Regulation of Innovations in the Medical Field: Experience in Counteracting Covid-19 - Fedorov, Valentyn; Kravchenko, Sergii; Reznichenko, Hanna; Opara, Nataliia; Tsybokhin, Oleg (Universidad Hemisferios, 2020)
The work is devoted to identifying the main problems of legal regulation of innovations in the medical field and developing the best options for solving them in the context of the Covid-19 pandemic. Thus, the research methodology is based on general and special scientific methods, in particular: formal legal, historical and legal, comparative analysis, and modeling. So, the procedure and issues to be considered are as follows. In the introduction, we will briefly highlight the origins of intellectual property rights issues in the medical field and the overall state of the pharmaceutical industry. In the first subsection of the third section, we will consider the positions of the main players in the pharmaceutical industry and the contradictions between them. In the second subsection, we will highlight the international obligations under TRIPS. In the third subsection, we will consider the consequences of their direct violation. In the fourth subsection, the impact of Covid-19 and the methods of legal regulation of medical innovations and patents under the TRIPS agreement will be discussed. In the fifth subsection, we will propose a way out and a compromise according to the Indian scenario. As a result of the study, contradictions were identified in the aspect of maintaining the balance of private and public interests between states and international pharmaceutical companies in the context of a pandemic and proposed ways to resolve them within the existing legal methods under the TRIPS agreement to achieve an acceptable compromise.